2017
DOI: 10.1111/1471-0528.14477
|View full text |Cite
|
Sign up to set email alerts
|

Assisted vaginal delivery in low and middle income countries: an overview

Abstract: This study, accomplished with the use of a variety of data sources from health care facilities in a number of developing countries, demonstrates quite clearly the overall relatively low use of assisted vaginal delivery (AVD, obstetrical forceps and the vacuum extractor) in most of the facilities. The information available to the investigators did not allow an assessment of the comparative risks and benefits of AVD in these settings. Not surprising was that factors responsible for the low use of AVD were low av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 26 publications
7
139
0
1
Order By: Relevance
“…The vacuum equipment used at this center comprises Kiwi vacuum extractors (Clinical Innovations, South Murray, Utah, USA), Bird and silicone cups, with hand and foot pumps. Forceps are available, but rarely used, as is the case in many hospitals in LMICs . Spinal anesthesia during cesarean delivery is provided by anesthetic nurses or anesthesiologists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vacuum equipment used at this center comprises Kiwi vacuum extractors (Clinical Innovations, South Murray, Utah, USA), Bird and silicone cups, with hand and foot pumps. Forceps are available, but rarely used, as is the case in many hospitals in LMICs . Spinal anesthesia during cesarean delivery is provided by anesthetic nurses or anesthesiologists.…”
Section: Methodsmentioning
confidence: 99%
“…Indications for this approach include fetal distress, prolonged second stage of labor, maternal exhaustion, or the need to avoid expulsive efforts among women with conditions such as heart failure or severe anemia . Although vacuum extraction can reduce maternal mortality from hemorrhage and sepsis—as well as perinatal mortality from birth asphyxia—use of this method has almost disappeared from obstetric practice in many LMICs . One study found that instrumental vaginal delivery was not used in almost half of 1728 Sub‐Saharan African hospitals, with usage rates below 1% in the remaining centers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of instrumental vaginal deliveries are conducted in the delivery room, but in a small proportion (2% to 5%), a trial of instrumental vaginal delivery is conducted in theatre with preparations made for proceeding to CD. ' A recent cross-sectional study on the use of assisted deliveries in 40 low-and middle-income countries in Latin America, sub-Saharan Africa and Asia [5] showed that only 1% of patients were delivered using AVD (either vacuum or forceps). The primary obstacle to performing an AVD was lack of healthcare workers trained in the procedure.…”
Section: In Practicementioning
confidence: 99%
“…8 OVB is underused precisely in countries where pregnant women continue to face hardships accessing emergency obstetric care and where Caesarean birth can be relatively unsafe. 9 OVB itself is not without risk. Furthermore, forceps and ventouse are associated with different risks and benefits, including long-term outcomes; there are different rates of perineal injury, and long-term possibilities of vaginal prolapse and incontinence associated with different modes of birth.…”
mentioning
confidence: 99%